What factors influence exclusive breastfeeding based on the theory of planned behaviour. (July 2018) - Zhang, Zhihong; Zhu, Yu; Zhang, Lijuan; Wan, Hongwei
Highlights: Breastfeeding knowledge is the most influential variable affecting exclusive breastfeeding. Month 1 and 2 were the months with high risk of weaning. Future intervention should especially target knowledge and continue to at least two months. Abstract: Objective: The primary objective is to investigate the related factors of exclusive breastfeeding based on the theory of planned behaviour (TPB) and identify the most influencing factor in first-time mothers at 4 postnatal months. Design and participants: A cross-sectional study was conducted and 400 first-time mothers at 4 months postnatal were approached. Measurements: Data on mothers' breastfeeding knowledge, attitude, subjective norm and practice control were collected at 4 months postnatal based on the TPB. The associations between these four factors and exclusive breastfeeding outcome were analysed using logistic regression and artificial neural network. Findings: Responses were acquired from 272 mothers. Exclusive breastfeeding rate was 34.4% at 4 months. About 66% and 79% mothers stopped breastfeeding their babies partially and absolutely during the first two postnatal months. Results showed that higher scores of breastfeeding knowledge (OR = 1.09, 95% CI = 1.04–1.14), attitude (OR = 1.04, 95% CI = 1.00–1.09), subjective norm (OR = 1.22, 95% CI = 1.11–1.34) and practice control (OR = 1.11, 95% CI = 1.02–1.20) were associated with a higher rate of exclusive breastfeeding. Among the four factors, breastfeeding knowledge was the utmost important factor contributing to exclusive breastfeeding. Key conclusions and implications for practice: Breastfeeding knowledge, attitude, subjective norm and practice control are positively related to exclusive breastfeeding based on the TPB. Future breastfeeding promotion intervention should target these four factors, especially breastfeeding knowledge, and continue for at least two postnatal months.